Does organic management of agroecosystems contribute to the maintenance of the richness of ants? - Daniela Roberta Holdefer (Semina: Ciências Agrárias, 2017)
Does organic management of agroecosystems contribute to the maintenance of the richness of ants? This study assessed the richness of ant species in organically farmed crop agroecosystems of different ages located in the southern state of Paraná, Brazil. During the sampling, the pitfalls that were active during May/August 2009 and from October 2009 to February 2010 were used. A total of 11,874 ants belonging to five subfamilies was sampled, comprising 18 genera and 48 species. The subfamily Myrmicinae (S = 27) had the highest richness, followed by the genera Pheidole (S = 10), Solenopsis (S = 7), Formicinae (S = 3), Camponotus (S = 5), and Brachymyrmex (S = 5). The average difference between the observed richness (Sobs) and the estimated richness (Chao2) was 10.9%. Ant assemblages belonging to agroecosystems under organic management for long times presented the greatest richness, indicating that this system contributes to the maintenance of ant diversity.